IMF deposition ceRNA network analysis and functional study of HIF1a in yak - Luo, Mengning; Wang, Hui; Zhang, Jun; Yixi, Kangzhu; Shu, Shi; Fu, Changqi; Zhong, Jincheng; Peng, Wei (Frontiers in Veterinary Science, 2023)
The concentration of intramuscular fat (IMF) is a crucial determinant of yak meat quality. However, the molecular mechanisms that regulate IMF in yak remain largely elusive.In our study, we conducted transcriptome sequencing on the longissimus dorsi muscle tissues of yaks with varying IMF contents. We then filtered differentially expressed genes (DEGs), microRNAs (DEMs), and long non-coding RNAs (DELs) to elucidate potential regulatory pathways of adipogenesis in yaks. Our results identified 469 DEGs (including GLB1L2, APC2, FABP4, and ELOVL6), 57 DEMs (including miR-1285-z, miR-122-y, miR-150-x, miR-130-x, and miR-3059-x), and 73 DELs (including MSTRG.12131.3, MSTRG.14096.1, MSTRG.1417.5, and MSTRG.347.2). Moreover, we constructed a competing endogenous RNA (ceRNA) co-regulation network based on these differential transcripts, pinpointing six sub-networks that may have a significant role in IMF deposition regulation in yaks. Among these, (novel-m0258-5p/novel-m0259-5p-MSTRG.12131.3-ENSBGRG00000010263, miR-3059-x-MSTRG.1417.5-CREG1, miR-3059-x-MSTRG.14098.1-ECHDC3, miR-10162-x-ENSBGRT00000028385-ENSBGRG00000000535, and miR-1285-z-MSTRG.347.2-ENSBGRG00000013053) were particularly noteworthy. Our in vitro cell experiments further demonstrated that the candidate gene, hypoxia-inducing factor (HIF1α), impeded the proliferation while facilitating the differentiation of yak intramuscular preadipocytes. Overall, our research sheds light on an array of potential mRNAs and noncoding RNAs implicated in IMF deposition and elaborates on the role of HIF1α in yaks.These findings contribute valuable insights that can serve as a guide for further research into the molecular mechanisms governing IMF deposition.